Coordination of Distributed Generators and Energy Storage Systems - Yu Wenpeng; Liu Dong; Huang Yuhui (Institute of Advanced Engineering and Science, 2014)
As the interconnection of distributed generation (DG) and energy storage system (ESS), the operation of DG/ESS should be optimized and coordinated. The intermittence of renewable energy and the error of the load forecasting, which is usually taken as the raw data of the global optimization algorithm, cause difference between the actual and the optimal operating status of the network. Feeder Control Error (FCE) is proposed based on the difference between the actual and the optimal net load of the network, and quantifies the operating error of the network. A coordinating control system of all the DG/ESS is proposed based on FCE, and 3 different control modes are put forwards. With the coordination system, the difference between the actual and the optimal net load are balanced by all the DG/ESS proportionally, and this reduces the operating error relative to the optimal operation status. DOI : http://dx.doi.org/10.11591/telkomnika.v12i4.4941